1994
DOI: 10.1111/j.1651-2227.1994.tb13276.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineralization after treatment of growth hormone deficiency in survivors of childhood malignancy

Abstract: Having noted symptomatic osteoporotic vertebral collapse in young adult survivors of childhood malignancy, bone mineral density (BMD) was examined at three sites by dual‐energy X‐ray absorptiometry in 64 patients treated in childhood for intracranial malignancy (group 1; n = 21) or acute leukaemia (group 2; n = 43). Patients in group 1 were selected for growth hormone deficiency (GHD) by auxological and biochemical criteria before the end of puberty (Tanner stage V). Seven patients (six men; mean (± SEM) age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 17 publications
0
40
3
Order By: Relevance
“…Because MTX is utilized in the treatment of childhood cancers, the present findings suggest that its effects on growing bones are complex and in need of further study. [36][37][38][39][40][41][42][43] While the clinical risk factors are multifactorial, specific chemotherapeutic agents, including high-dose MTX, ifosfamide, and bleomycin, have been implicated in causing bone loss. [43][44][45][46] By contrast, low-dose MTX in rats of age similar to ours (6 weeks) did not have a significant reduction in lumbar or femoral BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Because MTX is utilized in the treatment of childhood cancers, the present findings suggest that its effects on growing bones are complex and in need of further study. [36][37][38][39][40][41][42][43] While the clinical risk factors are multifactorial, specific chemotherapeutic agents, including high-dose MTX, ifosfamide, and bleomycin, have been implicated in causing bone loss. [43][44][45][46] By contrast, low-dose MTX in rats of age similar to ours (6 weeks) did not have a significant reduction in lumbar or femoral BMD.…”
Section: Discussionmentioning
confidence: 99%
“…10 Growth hormone presumably acts through changes in the production of insulinlike growth factor I (somatomedin C), which is a potent stimulator of skeletal growth, 25 thus suggesting a role for growth hormone in determining bone density. Children with acute leukemia who have received cranial radiation therapy and subsequently undergone BMT are at an increased risk for growth failure and growth hormone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Moreover, cranial irradiation 8,9 and growth hormone deficiency might be associated with decreased bone mineral density. 10 Sensitive methods are needed to demonstrate subCorrespondence: S Bhatia, at his current address: Division of Pediatric Hematology/Oncology, City of Hope National Medical Center, 1500, East Duarte Road, Duarte, CA 91010-3000, USA 5 Current address: University of Missouri Hospital and Clinics, Columbia, MI, USA Received 15 December 1997; accepted 10 February 1998 tle changes in bone accurately and assess therapeutic measures to correct demineralization. Several clinical and laboratory methods are typically used to assess osteopenia, but they have shortcomings.…”
mentioning
confidence: 99%
“…Survivors of brain tumors may be especially vulnerable to osteopenia as a result of growth hormone deficiency and hypogonadotropic hypogonadism due to cranial irradiation. 54 The large Childhood Cancer Survivor Study reported on more than 1600 survivors of brain tumors. Only 29 of them self-reported osteoporosis, and this disorder was more frequent than in their healthy siblings only in those who had received combined modality therapy 55 (surgery, radiation, and chemotherapy).…”
Section: Bone Mineral Loss and Cancer In Early Lifementioning
confidence: 99%
“…It should be noted that, in the initial report by Nussey et al, the determination of growth hormone deficiency was made in the majority of patients by clinical assessment and some of them had received spinal irradiation, 54 so the pathogenesis of osteopenia in that study was less than clear. Furthermore, retardation of height velocity and bone age during treatment occur in both irradiated and nonirradiated patients, and in both groups there is some catch-up after the completion of treatment, 114 emphasizing that, in children who receive multimodality therapy, cranial irradiation may not be the only contributor to osteopenia.…”
mentioning
confidence: 99%